20 years on the path – the criminal careers of Polish juvenile girls: 20 lat na ścieżce – kariery kryminalne polskich nieletnich dziewcząt (Archives of Criminology, 2023)
The ongoing research conducted at the Department of Criminology at the Institute of Law Studies of the Polish Academy of Sciences into juvenile delinquency resulted in establishing a database of persons who appeared before family and juvenile court for a punishable offence before 2000. The database enabled the continuation of research into the fate of juvenile girls, including and offered a unique insight into the lives of those individuals who continued to break the law in their adulthood. Court files studies were the basis of the analysis of juvenile girls’ offending at the time. Since then, the convictions of the juveniles in question has been verified three times: in 2011 (, in 2016 (for the period 2011-2015) and in 2018 (for the years 2016 and 2017). 836 juvenile girls remained that qualified for the research covering the period 2017-2019. From among this group 167 females were convicted of a criminal offence as adults, which is every fifth juvenile female in the study. For the sake of the research the research team decided to do in-depth research on the group of women that committed at least three offences in their adulthood, for which they had at least two convictions. Such established framework yielded 64 records (7.7% of the total juveniles in the research).